2020
DOI: 10.1007/s12064-020-00330-6
|View full text |Cite
|
Sign up to set email alerts
|

Are spliced ncRNA host genes distinct classes of lncRNAs?

Abstract: Many small nucleolar RNAs and many of the hairpin precursors of miRNAs are processed from long non-protein-coding host genes. In contrast to their highly conserved and heavily structured payload, the host genes feature poorly conserved sequences. Nevertheless, there is mounting evidence that the host genes have biological functions beyond their primary task of carrying a ncRNA as payload. So far, no connections between the function of the host genes and the function of their payloads have been reported. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…It remains an open question, however, if there are distinct classes of lncRNAs with different biological functions and/or molecular mechanisms, or whether the space of lncRNA functions and mechanisms rather form a densely populated continuum. A recent study of miRNA and snoRNA host genes suggests that the relationships between features, functions and mechanisms is likely far from simple [108]. It will likely be the case that typical lncRNAs are involved in multiple functions and take part in multiple molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It remains an open question, however, if there are distinct classes of lncRNAs with different biological functions and/or molecular mechanisms, or whether the space of lncRNA functions and mechanisms rather form a densely populated continuum. A recent study of miRNA and snoRNA host genes suggests that the relationships between features, functions and mechanisms is likely far from simple [108]. It will likely be the case that typical lncRNAs are involved in multiple functions and take part in multiple molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Small nucleolar RNA host genes ( Snhgs ), a type of lncRNA, serve as host genes for producing intronic small nucleolar RNAs (snoRNAs) and are mainly related to tumor pathophysiology by regulating proliferation, apoptosis, invasion, and migration (Sen et al, 2020, Zimta et al, 2020). Here, we found that the expression of hepatic Snhg3 was decreased in high-fat diet (HFD)-induced obesity (DIO) mice.…”
Section: Introductionmentioning
confidence: 99%